Long-term Survival After Hospital Admission in Older Italians: Comparison Between Geriatrics and Internal Medicine Across Different Discharge Diagnoses and Risk Status. (15th June 2020) - Di Bari, Mauro; Carreras, Giulia; Giordano, Antonella; Degli Esposti, Luca; Buda, Stefano; Michelozzi, Paola; Bernabei, Roberto; Marchionni, Niccolò; Balzi, Daniela
Abstract: Background: In randomized clinical trials, compared to Internal Medicine, admission to Geriatrics improved clinical outcomes of frail older patients accessing the Emergency Department (ED). Whether this advantage is maintained also in the "real world" is uncertain. We compared long-term survival of patients admitted to Geriatrics or Internal Medicine wards after stratification for background risk and across a variety of discharge diagnoses. Method: Data were derived from the "Silver Code National Project, " an observational study of 180, 079 unselected 75+ years old persons, admitted via the ED to Internal Medicine ( n = 169, 717, 94.2%) or Geriatrics ( n = 10, 362) wards in Italy. The Dynamic Silver Code (DSC), based on administrative data, was applied to balance for background risk between participants admitted to Geriatrics or Internal Medicine. Results: One-year mortality was 33.7%, lower in participants discharged from Geriatrics (32.1%) than from Internal Medicine (33.8%; p < .001), and increased progressively across four DSC risk classes ( p < .001). Admission to Geriatrics was associated with survival advantage in DSC class II to IV participants, with HR (95% CI) of 0.88 (0.83–0.94), 0.86 (0.80–0.92), and 0.92 (0.86–0.97), respectively. Cerebrovascular diseases, cognitive disorders, and heart failure were the discharge diagnoses with the widest survival benefit from admission to Geriatrics, which was mostly observed in DSC class III. Conclusions: Admission to Geriatrics may provide long-term survival benefit in subjects who, based on the DSC, may be considered at an intermediate risk. Specific clinical conditions should be considered in the ED to improve selection of patients to be targeted for Geriatrics admission.